Inhibition of Notch1 induces population and suppressive activity of regulatory T cell in inflammatory arthritis - Choi, Bo Youn (Theranostics, 2018)
Inhibition of Notch signalling has shown anti-inflammatory properties in vivo and in vitro models of rheumatoid arthritis (RA). The objective of this study was to determine whether Notch1 might play a role in regulating T-regulatory cells (Tregs) in animal models of RA. Methods: Collagen-induced arthritis (CIA) and collagen antibody-induced arthritis (CAIA) were induced in C57BL/6, Notch1 antisense transgenic (NAS) or DBA1/J mice. We examined whether pharmacological inhibitors of γ-secretase (an enzyme required for Notch1 activation) and antisense-mediated knockdown of Notch1 could attenuate the severity of inflammatory arthritis in CIA and CAIA mice. Proportions of CD4(+)CD25(+)Foxp3(+) Treg cells were measured by flow cytometry. To assess the suppressive capacity of Treg toward responder cells, CFSE-based suppression assay of Treg was performed. Results: γ-secretase inhibitors and antisense-mediated knockdown of Notch1 reduced the severity of inflammatory arthritis in both CIA and CAIA mice. Pharmacological and genetic inhibition of Notch1 signalling induced significant elevation of Treg cell population in CIA and CAIA mice. We also demonstrated that inhibition of Notch signalling suppressed the progression of inflammatory arthritis through modulating the expansion and suppressive function of regulatory T (Treg) cells. Conclusion: Pharmacological and genetic inhibition of Notch1 signalling suppresses the progression of inflammatory arthritis through modulating the population and suppressive function of Treg cells in animal models of RA.